Respuesta :

Answer:

KN = 11

Step-by-step explanation:

In right triangle LNM, by Pythagoras theorem:

[tex]LN=\sqrt{LM^2 -MN^2} \\ \\ \implies \: LN=\sqrt{ {(100)}^{2} -(80)^2} \\ \\ \implies \: LN=\sqrt{ 10000 -6400} \\ \\ \implies \: LN=\sqrt{ 3600} \\ \\ \implies \: LN=60[/tex]

In right triangle LNK, by Pythagoras theorem:

[tex]KN = \sqrt{LK^2-LN^2}[/tex]

[tex]\implies KN = \sqrt{(61)^2-(60)^2}[/tex]

[tex]\implies KN = \sqrt{3721-3600}[/tex]

[tex]\implies KN = \sqrt{121}[/tex]

[tex]\implies\huge{\orange{ KN =11}}[/tex]

Answer:

  • 11

[tex] \: [/tex]

Step-by-step explanation:

Before, Finding the length of KN, we must have to find the length of LN. So

[tex] \: [/tex]

Here, LNM is a right angled triangle where measure of two sides are given and we are to find the measure of the third side LN(Perpendicular).

[tex] \: [/tex]

We'll find the measure of third side with the help of the Pythagorean theorem.

[tex] \\ {\longrightarrow \pmb{\sf {\qquad (Base) {}^{2} + (Perpendicular {)}^{2} = (Hypotenuse {)}^{2} }}} \\ \\[/tex]

Here,

  • The base (NM) is 80

  • The perpendicular is LN

  • The hypotenuse (LM) is 100.

[tex] \: [/tex]

So, substituting the values in the above formula we get :

[tex]\\ {\longrightarrow \pmb{\sf {\qquad (NM) {}^{2} + (LN {)}^{2} = ( LM{)}^{2} }}} \\ \\[/tex]

[tex] {\longrightarrow \pmb{\sf {\qquad (80) {}^{2} + (LN {)}^{2} = ( 100{)}^{2} }}} \\ \\[/tex]

[tex] {\longrightarrow \pmb{\sf {\qquad (LN {)}^{2} = ( 100{)}^{2} - (80) {}^{2}}}} \\ \\[/tex]

[tex] {\longrightarrow \pmb{\sf {\qquad (LN {)}^{2} = 10000 - 6400}}} \\ \\[/tex]

[tex] {\longrightarrow \pmb{\sf {\qquad (LN {)}^{2} = 3600}}} \\ \\[/tex]

[tex] {\longrightarrow \pmb{\sf {\qquad LN = \sqrt{3600} }}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad LN = \frak{60}}}} \\ \\[/tex]

Therefore,

  • The length of LN is 60.

[tex] \\ [/tex]

As, we found the length of LN, now we can find the length of KN.

Where,

  • The base is KN

  • The perpendicular (LN) is 60.

  • The hypotenuse (LK) is 61.

So, in the right angled triangle LKN, by Pythagorean theorem we get,

[tex]\\ {\longrightarrow \pmb{\sf {\qquad (KN) {}^{2} + (LN {)}^{2} = ( LK{)}^{2} }}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad (KN) {}^{2} + {60}^{2} = ( 61{)}^{2} }}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad (KN) {}^{2} = ( 61{)}^{2} - {(60)}^{2}}}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad (KN) {}^{2} =3721 - 3600}}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad (KN) {}^{2} = 121}}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad KN = \sqrt{121} }}} \\ \\[/tex]

[tex]{\longrightarrow \pmb{\sf {\qquad KN = \frak{11} }}} \\ \\[/tex]

Therefore,

  • The length of KN is 11.
ACCESS MORE